REINVENSI KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) DI INDONESIA MENUJU AGENDA SUSTAINABLE DEVELOPMENT GOALS 2030 - Muftiadi, Anang; Rizal, Muhamad; Marselina, Mariana (Adbispreneur, 2023)
Achieving the target of drinking water access in SGDs 2030, Indonesia faces shortage of supply and development capacity, especially for PDAMs as service providers, so they need comprehensive strategies, considering the productivity, cost efficiency and sufficient profit level. Therefore, this study used measures the above three aspects, by using regression of 380 PDAMs data in Indonesia. Profit category consists of 1.3 percent of high profit PDAMs, 87.9 percent of profit, 9.5 percent of loss and 1.3 percent of huge loss. According to productivity, it shows that capital and number of employees has increasing return to scale. On the productivity categories, consist of 11.6 percent of high productivity,  42.65 percent of productive, 32.0 percent of less productive, and 13.8 percent of low productivity. According to the production cost category, all independent variables significantly affected the average cost. As many as 6.9 percent PDAM as high efficiency, 53.2 percent efficient, 25.4 percent less efficient, and 15.6 percent in-efficient. Then we have 32 PDAM categories of the three models with generic strategy option for individual PDAM strategies. Local governments as PDAM owners could use this model for development and performance increasement. In addition, sectoral ministries can utilize the 32 categories of PDAMs as basis for programs of facilitation, technical guidance, management and governance for achieving the SDGs 2030.Pencapaian target akses air minum pada SDGs 2030, Indonesia menghadapi keterbatasan pasokan dan kapasitas pengembangan, khususnya pada PDAM sebagai penyedia, sehingga membutuhkan strategi yang komprehensif, mempertimbangkan kategori produktivitas, efisiensi biaya hingga tingkat keuntungan yang mencukupi. Untuk itu, penelitian ini membahas ketiga aspek tersebut, menggunakan metode regresi dari data 380 PDAM di Indonesia.  Pada kategori Profit, sebanyak 1,3% tergolong profit tinggi, 87,9% memperoleh profit kecil, 9,5% rugi dan 1,3% rugi besar. Dari model produktivitas, bahwa kapital dan jumlah pegawai berpengaruh signifikan dan produksi bersifat increasing return to scale. PDAM Produktivitas tinggi sebanyak 11,6%, produktif 42,6%, kurang produktif 32,0% dan produktivitas rendah 13,8%. Dari model biaya produksi, seluruh variabel bebas signifikan mempengaruhi biaya rata-rata. PDAM efisiensi tinggi sebanyak 6,9%, efisien 53,2%, kurang efisien 25,4%, dan tidak efisien 14,6%. Dari ketiga bahasan, diperoleh 32 kategori PDAM dengan generic strategy masing-masing PDAM secara individual. Pemerintah daerah sebagai pemilik PDAM, dapat menggunakan model ini untuk arah pengembangan dan penyehatan. Selain itu kementerian teknis dapat memanfaatkan 32 kategori PDAM sebagai dasar kegiatan fasilitasi, pembinaan teknis, manajemen dan tata kelola agar dapat menjadi wahana pencapaian agenda SDGs 2030.